Learning Outside the Academy - Edwards, Richard; Gallacher, Jim; Whittaker, Susan (Taylor & Francis, 2006)
This book weaves together different strands of research in the area of lifelong learning that concentrates particularly on learning in alternative settings and ways, such experiential learning and informal and community learning. Drawing upon international research, the book examines how these strands of research can contribute to each other. The contributions to this book are based on material presented at a conference at the Centre for Research in Lifelong Learning, UK, and they focus on research into key issues of policy and practice in lifelong learning. Establishing a wider framework for debate about the meaning and significance of lifelong learning, this timely and thought-provoking book provides practitioners in the field with a relevant and current discussion on some very important ideas about non-formal education.